Neonatal Medicine in Iran: Current Challenges and Prospects - Golnaz Rezaeizadeh; Fatemeh Nayeri; Maryam Mahmoodi; Mamak Shariat; Shahrbanoo Nakhaei (Mashhad University of Medical Sciences, 2017)
Background: Pediatric medicine in Iran has been known as a specialty for more than 50 years; nevertheless, the neonatal-perinatal medicine is still in the first decades of its life. Regarding this, the present study was conducted toprovide an overall view of the current situation of the neonatal medicine, its challenges, and prospects in Iran.Methods: For the purpose of the study, a questionnaire was sent to 62 neonatologists via post or email. The collected data included the current condition of available equipment, facilities, and human resources in the neonatal wards. Furthermore, the neonatologists were asked about the most important step to be taken in terms of the neonatal health.Results: Out of the 62 neonatologist, who received the questionnaire, 38 (61%) cases filled out the instrument. Basedon the collected data, the presence of some services in the hospitals under investigation was reported to be indicative of some defects in the neonatal health system. These services included neonatal and pediatric development evaluation clinics (39.3%), psychology counseling sessions (25%), and access to placental and fetal pathology (53.3%). Significant shortage of human resources were mainly related to the lack of certain breast feeding consultant (25.7%), absence of social workers (24.1%), clinical pharmacists (75.9%), and genetic specialists (50%).Conclusion: As the findings of the present study indicated, the most important deficiency in our health system was the incomplete establishment of perinatal regionalization system.